2021
DOI: 10.1038/s41467-021-26611-2
|View full text |Cite
|
Sign up to set email alerts
|

Extent of myosin penetration within the actin cortex regulates cell surface mechanics

Abstract: In animal cells, shape is mostly determined by the actomyosin cortex, a thin cytoskeletal network underlying the plasma membrane. Myosin motors generate tension in the cortex, and tension gradients result in cellular deformations. As such, many cell morphogenesis studies have focused on the mechanisms controlling myosin activity and recruitment to the cortex. Here, we demonstrate using super-resolution microscopy that myosin does not always overlap with actin at the cortex, but remains restricted towards the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…Indeed, two recent studies suggest junctional heterogeneity reflects fluctuations of c-cadherin activity along mesenchymal cell-cell contacts (Huebner et al, 2021) as well as NMII-mediated contractility along the adherens junctions (Yang et al, 2022). Recent findings suggest NMII position within the cell cortex, either near to or more distant from the plasma membrane regulates mechanical properties of the cortex and allow rapid solid-to-fluid transitions in cell surface mechanics (Truong Quang et al, 2021). Since PCP complexes are localized in neuroectoderm at the level of adherens junction (Butler and Wallingford, 2017; Shimada et al, 2001), we propose that intra-junctional mechanical heterogeneity is coordinated through NMII activity and cadherin clustering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, two recent studies suggest junctional heterogeneity reflects fluctuations of c-cadherin activity along mesenchymal cell-cell contacts (Huebner et al, 2021) as well as NMII-mediated contractility along the adherens junctions (Yang et al, 2022). Recent findings suggest NMII position within the cell cortex, either near to or more distant from the plasma membrane regulates mechanical properties of the cortex and allow rapid solid-to-fluid transitions in cell surface mechanics (Truong Quang et al, 2021). Since PCP complexes are localized in neuroectoderm at the level of adherens junction (Butler and Wallingford, 2017; Shimada et al, 2001), we propose that intra-junctional mechanical heterogeneity is coordinated through NMII activity and cadherin clustering.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that NMII restricts junctional Pk2 movement by maintaining apical cortex compartmentalization. Moreover, NMII promotes mechanical heterogeneity within the junction, perhaps through the asymmetric accumulation of cadherins (Cavanaugh et al, 2022; Vanderleest et al, 2018) or by spatial control of fluid-solid transitions in the cortical actomyosin cytoskeleton (Truong Quang et al, 2021). This role of NMII, distinct from its involvement in contractility and modulation of junctional tension, leads to asymmetric repulsion of Pk2 puncta from posterior vertices.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the actin cortex itself is stratified, with myosin filaments being restricted toward the cytoplasmic side of the cortex due to steric exclusion from the dense cortex. 149 Interestingly, a recent in vitro reconstitution study showed that actin−myosin networks on SLBs spontaneously self-organize into radial actin structures (asters) with myosin at the core and layered atop to relieve steric constraints. 150 Mechanical measurements on cells indicate that the cortex adheres to the membrane via a high density of weak links.…”
Section: Involving the Membranementioning
confidence: 99%
“…Therefore, activation of the Rho-ROCK-myosin IIA pathway played a negative role in podosome formation and macrophage motility on the alternate non-adhesive surface. Spatial coordination of myosin and actin at the cortex regulates cell surface mechanics (18). Hence, we analyzed the relative localization of cortical actin and myosin IIA in macrophages on the alternate non-adhesive surface.…”
Section: Inhibition Of Myosin Iia Promotes Macrophage Motility On Alt...mentioning
confidence: 99%